Male rape : introducing a special provision in the penal code with reference to the laws in the United Kingdom / Muhammad Khairul Riduan Mustafar, Julie Faralisa Abd Jais and Muhammad Zulhilmi Mohd Nizam - Mustafar, Muhammad Khairul Riduan; Abd Jais, Julie Faralisa; Mohd Nizam, Muhammad Zulhilmi (2014)
This research is a study on the law of rape in Malaysia, namely the Penal Code ( Act 574 ). The issue of male rape by male which known as sodomy is something known to the country but not the issue of male rape by women where it happened overseas. There is no law regarding the criminal offence of male rape by women where there are possibilities which are unknown and might happen in future. The first stage of this study will involve information collecting and a review in seeking the rational for such law to be included in the Penal Code in order to protect all. The issue of gender equality is one of the reasons why such law should have here. Elements of consent and medical are also the arguments here as it is important in establishing male rape by women. This study then will be followed by the qualitative analysis which are the views and opinions from the subject to the questions asked.